COMMUNITY SERVICE EDUCATION ON NUTRITIONAL PATTERNS AND TABOOS IN BATAK CULTURE RELATED TO NUTRITION FOR PREGNANT WOMEN IN MEDAN TUNTUNGAN DISTRICT - Noer Desmie; Leni Agustina; Indah Lestari Sitorus (Cattleya Darmaya Fortuna, 2024)
The health of pregnant women is the main indicator of well-being which is highly dependent on nutritional adequacy during pregnancy. However, in Medan Tuntungan District, the nutritional fulfillment of pregnant women is still hampered by cultural factors, especially the belief in the